Formulation Development and Compatibility Study for BTD (Brimonidine Tartrate, Timolol Maleate, and Dorzolamide HCl) used in the Management of Glaucoma Disease - Venkateswaran, Dr. J. (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: The main objective of the present study was to develop a stable formulation and manufacturing process of fixed dose combination of antiglaucoma drug (BTD) which contains brimonidine tartrate, timolol maleate, and dorzolamide hydrochloride. Materials and Methods: Compatibility study with regard to product contact materials such as platinum-cured silicone tube, SS 316L (metal), and nylon membrane filter was evaluated by analysis of their description, pH, and assay using instruments such as pH meter and high-performance liquid chromatography (HPLC). Results: Formulations were analyzed and results were found well within specified limits. BTD formulation was prepared by dissolving all the ingredients in water for injection under continuous stirring, and the solution was filtered through sterilized 1.2 Î¼ nylon pre-filter and followed by 0.2 Î¼ nylon filter. Conclusion: Compatibility study was performed to evaluate the physical and chemical stability of BTD formulation, and all data indicate that BTD formulation was physically compatible and chemically stable.